The effects of deterrence factors on income tax evasion among Palestinian SMEs - Alkhatib, Amjad Abdallah; Abdul Jabbar, Hijattulah; Marimuthu, Munusamy (Human Resource Management Academic Research Society, 2018)
Tax evasion remains an issue confronting most policy makers worldwide. Palestine, as an evolving developing country highly depends on tax revenue and funds from international aids to finance the country’s growth plan.The current study aims at examining relationships between probability of detection, tax penalty, tax rate and income tax evasion by applying the Deterrence Theory. A proportionate sampling technique was employed to collect data for the study through the use of questionnaires. The total number of useable questionnaires collected for analysis was 184. The collected data were analysed using the Partial Least Square (PLS). The result of analysed data shows that probability of detection and tax penalty were found to be negatively significant, while tax rate was positively significant in relation to income tax evasion. The implication of the findings of the current study is that income tax administration effectiveness can maximize tax collections and discourage tax evasion.